Urinary melatonin levels in children with atopic dermatitis and healthy controls - Dwi Ratna Adisty; Iskandar Zulkarnain; Diah Mira Indramaya (PAGEPress Publications, 2019)
Melatonin an important immunomodulatory molecule in allergic diseases. Melatonin also plays a role in several body systems including to regulate circadian rhythms because of its role to cause drowsiness. Research shows in the case of atopic dermatitis (AD) circadian production of melatonin is reduced compared to healthy controls. This study aimed to investigate the differences of urinary melatonin levels between children with AD and healthy controls, and its relationship with disease severity. A cross sectional study was conducted in pediatric dermatology division of our outpatient clinic. Severity of AD was determined by using the instruments Scoring Atopic Dermatitis (SCORAD). Urinary melatonin levels were measured by Enzyme-linked immunosorbent assay (ELISA). The urinary melatonin levels in AD group were not significantly lower than in healthy controls (P =0.98 P<0.05) but the means show lower levels of urinary melatonin levels in AD group (486.73 ± 292.13 pg/ml , 611.51 ± 280.45 pg/ml, respectively). There were no significant association between urinary melatonin levels and disease severity (P > 0.05) but there's a tendency of decreased urinary melatonin with increased the severity of AD.